The Effect of Good School Governance Implementation on BOS Fund Management with Human Resource Competence as a Moderating Variable: An Empirical Study at Senior and Vocational High Schools in Subang Regency - Destia, Sella; Silviana, Silviana (DINASTI RESEARCH, 2025)
This research aims to analyze the effect of implementing Good School Governance on the management of School Operational Assistance (BOS) funds, as well as examine the role of human resource (HR) competence as a moderating variable. The background of this research stems from various issues in BOS fund management, including lack of transparency, accountability, and cases of fund misuse, which indicate the suboptimal application of good school governance principles. This research uses a quantitative method with primary data collected through questionnaires distributed to 77 respondents from 21 senior high schools (SMA) and 16 vocational schools (SMK) in Subang Regency, consisting of principals, teachers/education staff, and school operators. The results show that Good School Governance has a significant effect on BOS fund management, with a significance value of 0.000. Furthermore, HR competence significantly moderates the relationship between Good School Governance and BOS fund management, also with a significance value of 0.000. These findings highlight the importance of applying good governance principles and improving HR competence to ensure transparent, accountable, and efficient BOS fund management.